ANALISIS PERBANDINGAN KINERJA KEUANGAN ANTARA PERUSAHAAN FARMASI MILIK NEGARA (BUMN) DENGAN PERUSAHAAN FARMASI MILIK SWASTA (BUMS) YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2015-2019) - Wahyudi, Aguna Anugraha; Hermawan, Hendy (Universitas Nusantara PGRI Kediri, 2021)
This study aims to examine the comparison of financial performance between state-owned companies and privately-owned companies in the pharmaceutical industry listed on the Indonesia Stock Exchange for the 2015-2019 period. The variables used to compare financial performance are Current Ratio (CR), Net Profit Margin (NPM), Operating Profit Margin (OPM), Return On Asset Ratio (ROA). This type of research is a comparative study. The research sample consisted of 11 companies consisting of 3 state-owned pharmaceutical companies and 8 private pharmaceutical companies. The sample was selected using the purposive sampling method. The research data were analyzed with SPSS version 26 using parametric statistical tests, namely the independent sample t-test. The results of the study using the two-average difference test showed that there was no significant difference in financial ratios consisting of OPM, NPM, and ROA between state-owned pharmaceutical companies and private-owned pharmaceutical companies listed on the Indonesia Stock Exchange during the study period. While the CR there is a significant difference between the two in the study period. Overall, the financial performance of privately-owned pharmaceutical companies is better than that of state-owned pharmaceutical companies listed on the Indonesia Stock Exchange in the study period